Retrato de uma Unidade Saúde Escola durante a pandemia da COVID-19: caracterização dos novos usuários e das estratégias de atendimentos - Frederico, Isabel Cristina (2022)
The discussion field of this work is the current situation of human illness and the reality of Brazilian public health system. Humanity is experiencing an unexpected and unplanned crisis with the COVID-19 pandemic. The School Health Unit (USE) of the Federal University of São Carlos (UFSCar) is part of the health care network as a Multidisciplinary Academic Unit and its mission is to train people through interprofessional health care, based on the dissociability between teaching, research and extension, prioritizing the humanization and integrality of care. The USE has actively participated on health care attention to the general population, mainly by actions in the last two years related to the COVID-19 pandemic, adopting and developing measures to meet the users demands due to the need for social isolation. The objective of the present research is to describe the health care system developed at USE in the first two years of the COVID-19 pandemic, focusing on the sociodemographic characterization of users and the new modality of remote care. The method is of a documented research of quantitative and qualitative nature, which aimed to compute sociodemographic information (Step 1) as well as identify and characterize the new service proposals together with the technologies developed by professionals at the Unit (Step 2). In this second part, data records collected from 2019 on, related to the origin of the user (such as referred unit), diagnosis, complaints, areas of registration in the Unit and the extension actions offered in the new modalities of health care, via remote access, are presented. In Steps 1 and 2, the information was extracted from the USE database (USEWEB), and the treatment of such data required simple statistical procedures. The results revealed that, in 2019 and the first two years of the COVID-19 pandemic, the USE attended a greater number of women and people who declared themselves white, followed by those who declared themselves to be black or brown, most of them single and adult. For the income and the prevailing level of education, there is a variation between 1 and 5 minimum wages and a majority having reached high school. As for the professional situation, different types of jobs and retired people were observed. In the studied period, there was a significant number of absence of information registration. The results also reveal that the Integrative Mental Health Outpatient Clinic received the highest volume of enrollments both in 2020 and in 2021; that USE, through technical professionals, teachers and students, developed remote health actions, in an innovative way, through extension projects, to assist people during the pandemic. The data indicate a considerable drop in the number of enrollments, between the years 2020 and 2021, compared to previous years, and the lowest access to USE services was for low-income people. It is concluded that the Health School Unit acted in an innovative way, reorganizing its work processes, during the first years of the pandemic in the provision of health care to the population through virtual resources. The sociodemographic characterization showed that, although the number of consultations was reduced during the pandemic, the profile of users was maintained. For future research, it is suggested to investigate the causes responsible for the high rate of missing data in the Unit's electronic system, fundamental data for the planning, organization and evaluation of its own services.